Community-Based Experiential Education: Making It Meaningful to Students Means Making It Meaningful for Everyone. Issue 2 (1st September 2017) - Gallant, Karen; Fenton, Lara; Hamilton-Hinch, Barbara; Hutchinson, Susan; Rehman, Laurene; Singleton, Jerome
Abstract: This research project explored students' and community practitioners' experiences of community-based experiential education and, in particular, the characteristics of such experiences that are key to creating meaningful learning opportunities. Through focus groups with current undergraduate students in recreation programs at Dalhousie University, Nova Scotia, Canada, and key informant interviews with practitioners at community organizations that have facilitated experiential education for our students, we explored the research question: What aspects of community-based experiential education are key to creating meaningful learning opportunities for recreation students? Based on our thematic analyses, the data can be described by the three themes of value, context, and relationships. Overall, findings suggest that all stakeholders in the experience—instructors, students, and community practitioners—need to find their involvement meaningful, and that the meaningful nature of such experiences is associated with mutual value, deep relationships, and a supportive context.